2018
DOI: 10.2147/nss.s186665
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in patients with liver cirrhosis: prevalence, impact, and management challenges

Abstract: Sleep–wake disturbances are common in liver cirrhosis and associated with impaired quality of life. The most common abnormalities are insomnia (difficulties falling asleep and maintaining sleep, or unrefreshing sleep), excessive daytime sleepiness, and sleep–wake inversion (disturbances of circadian rhythmicity). The underlying pathophysiological mechanisms for sleep disturbances in cirrhosis are complex and may include disturbed metabolism of melatonin and glucose, alterations in thermoregulation, and altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…Subjective tools, such as questionnaires, e.g. ESS and Berlin questionnaires, can be used to collect information on sleep quality and daytime complaints while objective methods such as PSG allow more precise assessment [ 14 ], and this was obvious in the current study; by questionnaire SBD is 33.3% while by PSG the prevalence is higher at 56.2%. This is due to the fact that patients, especially insomniacs, tend to underestimate their sleep quality.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Subjective tools, such as questionnaires, e.g. ESS and Berlin questionnaires, can be used to collect information on sleep quality and daytime complaints while objective methods such as PSG allow more precise assessment [ 14 ], and this was obvious in the current study; by questionnaire SBD is 33.3% while by PSG the prevalence is higher at 56.2%. This is due to the fact that patients, especially insomniacs, tend to underestimate their sleep quality.…”
Section: Discussionmentioning
confidence: 96%
“…First, the number of patients recruited is small. Second, the study lacks both in depth analysis of the prior episodes of HE and testing for minimal HE, because HE by itself is associated with sleep disorders among cirrhotics [ 14 ] and one study concluded that prior HE may synergize with OSA in worsening sleep patterns in cirrhotics [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver physiology and pathophysiology are subjected to a tight circadian regulation, mostly influenced by feeding time [ 294 ]. Circadian disturbances, such as alterations in the sleep–wake cycle and disrupted patterns of hormones secretion are common risk factors associated with liver cirrhosis, a previous step to develop liver cancer (LC) [ 295 ]. Hepatocellular carcinoma is the most abundant type of LC and the fourth leading cause of cancer death worldwide according to the World Health Organization (WHO) [ 296 ].…”
Section: Melatonin: Reported Actions In Breast Prostate Liver Amentioning
confidence: 99%
“…Traditionally, hepatic encephalopathy (HE) has been incriminated as the main cause for sleep disorders, but recent studies [ 2 , 3 , 4 , 5 , 6 ] have reported sleep abnormalities in patients without neurocognitive disorders attributable to HE. Among the possible incriminated mechanisms have been mentioned imbalances of melatonin metabolism, imbalances of thermoregulation, and increased level of serum ammonia that crosses the blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%